Adjoint tomography of northeast Japan revealed by common-source double-difference travel-time data - Chen, Jing (2022)
We present the wave equation-based adjoint tomography of northeastern Japan using common-source double-difference travel-time data. More than 30,000 high-quality first P-wave arrivals from 117 local earthquakes recorded by 713 seismic stations are included in the inversion, generating more than 350,000 double-difference travel times of first P-wave arrivals. In comparison with commonly used travel-time data, the common-source double-difference travel times are insensitive to source parameters and source-side structures but place enhanced constraints on receiver-side structures. As a result, these robust double-difference travel times generate a reliable VP model down to a depth of 120 km. Our inversion results clearly show crustal low-velocity anomalies beneath the volcanic arc. The subducting Pacific slab is illuminated as a landward-dipping high-velocity anomaly, and the arc magmatism in the mantle wedge is shown as low-velocity anomalies. Thanks to the newly operated Seafloor Observation Network (S-net), prominent high-velocity bodies are detected in the fore-arc mantle wedge at depths of 30-60 km. These abnormal high-VP bodies indicate a low degree of serpentinization in the fore-arc mantle wedge at low temperatures, correlating well with the previous finding that the uppermost mantle in the Kuril and Tohoku fore-arc is cold and dry.Our inversion results reveal reliable tectonic features in the subduction zone beneath northeastern Japan, suggesting thatwave equation-based common-source double- difference travel-time adjoint tomography is an effective and robust method to illuminate detailed structures of the crust and uppermost mantle.